A statutory duty of candour: The pros and cons of imposing the duty on individuals. (January 2014) - Kemp, Sophie
In the wake of the Mid Staffordshire Public Inquiry, this paper considers the arguments for and against the imposition of a statutory duty of candour on individuals, examining the validity of claims that such a duty would result in greater secrecy among healthcare professionals and lead to defensive practice. Examination of arguments for imposing an individual duty, highlights the pre-existing moral obligation on healthcare professionals to inform patients who have suffered harm, has not yet been sufficiently embedded throughout the NHS by professional codes of conduct, and the need to establish systematic formalised error reporting in order to continue to minimise clinical error.